Clinical aspects of pregnancy and childbirth in women with intrahepatic cholestasis of pregnancy - CEMORTAN, Maria; SAGAIDAC, Irina; ILIADI-TULBURE, Corina; CERNETCHI, Olga (One Health & Risk Management, 2024)
Introduction. Intrahepatic cholestasis of pregnancy (ICP) is a liver pathology that has negative impact on progression of pregnancy and childbirth in affected women. This study aims to assess the clinical characteristics of pregnancy and delivery among women diagnosed with intrahepatic cholestasis of pregnancy. Material and methods. The study was conducted as a prospective cohort study involving 142 clinical cases, divided into two groups according to the complication of pregnancy with cholestasis gravidarum. Evaluation of pregnancy and childbirth clinical aspects was performed alongside an examination of medical records. Statistical data were processed using IBM Statistics SPSS 21, MedCalc and GraphPad software. Results. It was determined that every fourth pregnant woman diagnosed with intrahepatic cholestasis of pregnancy also presented with hyperemesis gravidarum during the current pregnancy. Additionally, an elevated prevalence of iron deficiency anemia and gestational diabetes mellitus was detected among pregnant women with this condition. Meconium staining of the amniotic fluid complicated approximately one in every four pregnancies in women with intrahepatic cholestasis gravidarum. Conclusions. The study findings indicate a notable increase in hepato-biliary conditions and nephrourinary pathology among women with ICP. Hence, a high incidence of hyperemesis gravidarum, along with an elevated frequency of iron deficiency anemia and gestational diabetes mellitus, was found in women with this condition.